GE_GERICHTE P/10859/2020 vom 23. August 2020 - GE Cour de justice (2020)
BASE DE DONNÉES;EMPREINTE DIGITALE;DESSAISISSEMENT;MINORITÉ(ÂGE);COMPÉTENCE;MAJORITÉ PÉNALE;PREUVE;APPRÉCIATION DES PREUVES | CPP.251; CPP.139; CPP.182; DPMin.3